2021
DOI: 10.1177/14644207211035520
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of B4C amount and sintering temperature on the thermal properties of the material in Al 1070–B4C composites

Abstract: Today, the usage area of metal matrix and ceramic reinforced composites is increasing and researches in this field are increasing. However, majority of the studies conducted are constituted of studies on investigation of mechanical features of composites. One of the reasons why composite materials are preferred is because these materials have improved thermal property. With this experimental study, it is aimed to contribute to the literature in the area of investigating features of thermal properties. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Due to the structural dissimilarity of graphene oxide in the aluminium matrix, there are difficulties in its homogeneous distribution in the matrix. For that reason, the studies on surface strengthening of graphene oxide added AMC have been carried out by using techniques such as stirred casting, liquid metal impregnation, sprayed deposition casting and so on (Toptan et al, 2010;Fadavi Boostani et al, 2018;Wu et al, 2019;Zheng et al, 2020a;Pehlivanlı & Pul, 2021). However, no study has been found on the graphene oxide-added AMCs with stirred casting so far using surface hardening processes like shot peening (Sun et al, 2018;Zhu et al, 2019;Rozhbiany & Jalal, 2019;Sasikumar et al, 2020) With the shot peening process, the surface of the graphene oxide structured AMC will be hardened by a massive amount of high hardness and high-speed kinetic energy projectiles (Zhu et al, 2016;Zhan et al, 2018a;Zhan et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the structural dissimilarity of graphene oxide in the aluminium matrix, there are difficulties in its homogeneous distribution in the matrix. For that reason, the studies on surface strengthening of graphene oxide added AMC have been carried out by using techniques such as stirred casting, liquid metal impregnation, sprayed deposition casting and so on (Toptan et al, 2010;Fadavi Boostani et al, 2018;Wu et al, 2019;Zheng et al, 2020a;Pehlivanlı & Pul, 2021). However, no study has been found on the graphene oxide-added AMCs with stirred casting so far using surface hardening processes like shot peening (Sun et al, 2018;Zhu et al, 2019;Rozhbiany & Jalal, 2019;Sasikumar et al, 2020) With the shot peening process, the surface of the graphene oxide structured AMC will be hardened by a massive amount of high hardness and high-speed kinetic energy projectiles (Zhu et al, 2016;Zhan et al, 2018a;Zhan et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%